2022
DOI: 10.1021/acsami.2c00987
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of a 3D Porous Aligned Graphene-Based Wall Network Architecture by Confined Self-Assembly with Shape Memory for Artificial Muscle, Pressure Sensor, and Flexible Supercapacitor

Abstract: The development of a novel preparation strategy for 3D porous network structures with an aligned channel or wall is always in challenge. Herein, a 3D porous network composed of an aligned graphenebased wall is fabricated by a confined self-assembly strategy in which holey reduced graphene oxide (HrGO)/lignin sulfonate (Lig) composites are orientedly anchored on the framework of the Lig/single-wall carbon nanotube (Lig/SWCNT) hydrogel by vacuum-assisted filtration accompanied with confined self-assembly and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…As the concentration of polymer increases, the role the composite polymer material plays in surface functionality increases while the surface properties of the LIG decreases. , Interestingly, the use of LIG to pattern paper surfaces has been suggested as a new tool for generating artistic designs on paper substrates, and the electrical conductivity of LIG might lead to additional in-built functionality . Other recent advances in LIG processing technology include the use of modified three-dimensional (3D) printing processes derived from laminated object manufacturing to make 3D LIG foams, , substituting the CO 2 laser for visible light and UV laser sources to scribe LIG, , using laser direct writing technologies to fabricate LIG, and monolithic fabrication processes, among others. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the concentration of polymer increases, the role the composite polymer material plays in surface functionality increases while the surface properties of the LIG decreases. , Interestingly, the use of LIG to pattern paper surfaces has been suggested as a new tool for generating artistic designs on paper substrates, and the electrical conductivity of LIG might lead to additional in-built functionality . Other recent advances in LIG processing technology include the use of modified three-dimensional (3D) printing processes derived from laminated object manufacturing to make 3D LIG foams, , substituting the CO 2 laser for visible light and UV laser sources to scribe LIG, , using laser direct writing technologies to fabricate LIG, and monolithic fabrication processes, among others. , …”
Section: Introductionmentioning
confidence: 99%
“…8,16 Interestingly, the use of LIG to pattern paper surfaces has been suggested as a new tool for generating artistic designs on paper substrates, and the electrical conductivity of LIG might lead to additional in-built functionality. 19 Other recent advances in LIG processing technology include the use of modified threedimensional (3D) printing processes derived from laminated object manufacturing to make 3D LIG foams, 20,21 substituting the CO 2 laser for visible light and UV laser sources to scribe LIG, 22,23 using laser direct writing technologies to fabricate LIG, 24 and monolithic fabrication processes, 25 among others. 26,27 Here we show that various artistic LIG designs can also be embedded into the composite material of concrete and tailored to their desired application.…”
Section: Introductionmentioning
confidence: 99%
“…These oxygen-containing functional groups are present in components of wood (cellulose, lignin, and hemicellulose) and reportedly undergo redox reactions (quinone ↔ hydroquinone) within the potential range of 0–0.55 V (vs Ag/AgCl). Therefore, the CV curves of CNT@FW-RC and CNT@NW-RC show broad redox peaks along with a rectangular capacitor-like behavior. , …”
Section: Resultsmentioning
confidence: 98%
“…The electrochemical performance of rGO/GSP-3 is obviously better than those of other reduced graphene materials reported in the literature, such as a Prussian blue/ reduced graphene oxide electrode (PB/rGO, 286 F g −1 @ 0.3 A g −1 and 154 F g −1 @ 10 A g −1 ), 46 oligo(p-phenylenevinylene)/rGO (OPVs@rGO, 181 F g −1 @ 1 A g −1 ), 47 poly(ionic liquids)/rGO (PILs/rGO, 160 F g −1 @ 2 A g −1 ), 48 and sodium lignosulfonate/single-walled carbon nanotube/ rGO (Lig/SWCNT/rGO, 249 F g −1 @ 1 A g −1 ). 49 EIS measurements were further conducted to measure the influence of GSP content on the capacitive performance of rGO/GSP electrodes, as shown in Figure S4. It is shown that the plots of all samples exhibit a small semicircle at high frequency and a vertical line at low frequency, attributed to a low charge transfer and diffusion resistance at the electrolyte/ electrode interface, which is a further indication of the effective reduction of GO and nearly ideal electrochemical properties.…”
Section: Electrochemical Properties In a Three-electrode Systemmentioning
confidence: 99%